EFEKTIVITAS PROGRAM KELUARGA HARAPAN DI DESA RUMBUK TIMUR KECAMATAN SAKRA - M. Febrian Maulana W; Sahar, Sahar; Rosita, Rosita (Nusantara Hasana Journal, 2025)
This study examines the effectiveness of the Family Hope Program (PKH) in Rumbuk Timur Village, Sakra District. PKH plays a role in improving the welfare of low-income communities through financial support, access to education, healthcare services, and economic empowerment. The findings indicate that PKH contributes to reducing school dropout rates, expanding access to healthcare, and promoting community self-sufficiency. However, challenges remain, such as delays in fund disbursement and inadequate monitoring by program facilitators. Improvements in fund disbursement and the monitoring system are necessary to enhance PKH’s effectiveness in reducing poverty and improving the quality of life for the community. The results also show that PKH has a sustainable impact on improving community welfare in Rumbuk Timur Village. This program not only helps reduce school dropout rates and expand access to healthcare services.